Pengembangan Model Self Regulation Berbasis Protection Motivation Theory Terhadap Manajemen Perawatan Diri Pada Pasien Gagal Jantung: A Literature Review - Pratama, Shafaat; Sriyono, Sriyono; Wahyudi, Andri Setiya (Universitas Tribhuwana Tunggadewi, 2023)
Factors affecting recurrent hospitalization in patients with heart failure are non-compliance with medication, fluids, and diet. Compliance with medication, dietary and fluid restriction, and weight of the body are part of self-care management. The study aims to improve self-care management in heart failure patients. Literature reviews are used to identify articles through Scopus, ProQuest, PubMed, and CINAHL databases. The inclusion criteria are open access, in English, with full-text articles published between 2016 and 2022 with the keywords